The social and symbolic context of the royal potters of Buganda : - Giblin, John D.; Kigongo, Remigius (Archaeological Research in Africa, 2012)
This paper describes the technical activities of the contemporary makers of the royal pots of Buganda and the social context of this technology and its products, alongside the symbolic world of which these are a part. The ethnoarchaeological research presented here suggests that Ganda pottery was not only a technical and functional product, but was also socially and symbolically constructed, reflecting the moral values of society. This paper identifies pottery in Buganda as a symbolic source of health, which has resulted in the establishment of royal potters who make ritually clean royal pots by following strict taboos in order to protect the health of the kabaka (king) and the kingdom. The unfortunate archaeological implications of this work are that it may be the intangible and archaeologically elusive activities of the royal potters that make their pots royal are not necessarily the tangible ones.
Azania: Archaeological Research in Africa